Ototoxicity of Polymyxin B, Neomycin, and Hydrocortisone Suspension in Tympanoplasty Surgery. (February 2014) - House, James R.; House, Laura K.
Objectives: (1) To determine the safety of using a commercially available suspension of polymyxin B, neomycin, and hydrocortisone (PNH) in tympanoplasty surgery. (2) To apply evidence-based medicine to tympanoplasty surgery when considering potential ototoxicity. Study Design: Case series with chart review. Setting: Tertiary otology practice, single surgeon. Methods: Approval for this study was obtained from the St. Dominic–Jackson Memorial Hospital Institutional Review Board. Data were gathered on 272 consecutive type 1, underlay tympanoplasties for which both pre- and postoperative audiometric data were available over a 10-year period. In each surgery, gelatin sponge saturated in a commercially available PNH suspension was placed in the middle ear to support the graft. Patients ranged in age from 3 years to 79 years. Preoperative and postoperative bone conduction thresholds were measured at 500, 1000, 2000, 3000, and 4000 Hz. Results: The average change in sensorineural hearing as measured by bone conduction thresholds was negligible, with a slight improvement in all frequencies tested except 4000 Hz. The changes by frequencies were as follows: 500 Hz (–1.624 dB), 1000 Hz (–1.399 dB), 2000 Hz (–0.975 dB), 3000 Hz (–0.596 dB), and 4000 Hz (+0.560 dB). The 5-frequency average change was −0.545 dB. Conclusions: The commonly used otic solution containing polymyxin B, neomycin, and hydrocortisone demonstrates no ototoxicity in tympanoplasty surgery and is safe to use in this setting.